Orbital mechanics - Chobotov, Vladimir A. (American Institute of Aeronautics and Astronautics, 2002)
Annotation Designed to be used as a graduate student textbook and a ready reference for the busy professional, this third edition of "Orbital Mechanics is structured so that you can easily look up the things you need to know. This edition includes more recent developments in space exploration (e.g. Galileo, Cassini, Mars Odyssey missions). Also, the chapter on space debris was rewritten to reflect new developments in that area. The well-organized chapters cover every basic aspect of orbital mechanics, from celestial relationships to the problems of space debris. The book is clearly written in language familiar to aerospace professionals and graduate students, with all of the equations, diagrams, and graphs you would like to have close at hand. An updated software package on CD-ROM includes: HW Solutions, which presents a range of viewpoints and guidelines for solving selected problems in the text; Orbital Calculator, which provides an interactive environment for the generation of Keplerian orbits, orbital transfer maneuvers, and animation of ellipses, hyperbolas, 'and interplanetary orbits; and Orbital Mechanics Solutions
Keywords: Orbital mechanics.; Artificial satellites -- Orbits.; Navigation (Astronautics); elektronické knihy; electronic books